DENTAL TECHNOLOGY EDUCATION IN ESTONIA: STUDENT RESEARCH IN TALLINN HEALTH CARE COLLEGE - Kuuse, Heli; Pihl, Toomas; Kont, Kate-Riin (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The aim of this article is to give an overview of the best dental technician student research in Tallinn Health Care College. In their graduation theses, students investigated the mechanical properties of avilable materials in dental technology. The students’ main interest was to find out what happens in a situation where dental technology materials are used differently from the manufacturers’ recommendations, e.g. if the components are mixed in wrong proportions. Students prepared (7-10 pieces) test bodies in a dental technology laboratory. Tests and measurements were carried out at TTK University of Applied Sciences. The test spectrum using the Universal Material Tester G.U.N.T WP 300 covers tensile tests, compression tests, bending tests, and hardness tests. Expansion measurings are procedures that have been developed using digital calipers and a feeler gauge. The encouragement of student involvement in a research project is most important for dental technician education. Incorrect handling of materials can affect the durability of dental prostheses; weaken the quality of dental prostheses; influence the suitability of dental prostheses in the oral cavity. The reasons for improper handling of dental materials: dental technicians do not read the manual carefully; dental technicians have “a lot of work”; working by force of habit; patient needs the denture as soon as possible. Keywords: dental technician curriculum, students’ research, alginate impression material, cold- and heat-cured acrylic, denture teeth bonding to acrylic, orthodontic wire, dental gypsum, tensile strength, compressive strength, expansion, adhesion strength, flexural strength